Fully-integrated medical home for people with severe and persistent mental illness: A description and outcome analysis of a Medicare Advantage Chronic Special Needs Program - Robert Myers (Mental Illness)
People with severe persistent mental illness pose a significant challenge to managed care organizations and society in general. The financial costs are staggering as is the community impact including homelessness and incarceration. This population also has a high incident of chronic comorbid disorders that not only drives up healthcare costs but also significantly shortens longevity. Traditional case management approaches are not always able to provide the intense and direct interventions required to adequately address the psychiatric, medical and social needs of this unique population. This article describes a Medicare Advantage Chronic Special Needs Program that provides a Medical Home, Active Community Treatment, and Integrated Care. A comparison of utilization and patient outcome measures of this program with fee for service Medicare found significant reduction in utilization and costs, as well as increased adherence to the management of chronic medical conditions and preventative services.